The effect of locked screw angulation on the biomechanical properties of the S.P.S. Free-Block plate - Merino, M. K A [UNESP]; Rahal, Sheila Canevese [UNESP]; Ribeiro, C. R.; Padovani, C. R. [UNESP] (Thieme, 2013)
Objectives: Among the locked internal fixators is one denominated S.P.S. (Synthesis Pengo System) Free-Block, which was designed with a locking ring that allows the screw to be locked and positioned obliquely. Due to the paucity of biomechanical studies on this system, the present work aimed to evaluate the influence of locked screw angulation on the resistance of the S.P.S. Free--Block plate. Methods: Forty synthetic bone cylinders with 10 mm fracture gap were used. Forty seven-hole 3.5 mm stainless steel plates (two AO-like dynamic compression holes and five locked holes) were assembled according to the orientation of the locked screws: mono cortical screws were positioned at 90° to the long axis of the cylinder (Group 1), and monocortical screws were positioned at 70° to its cylinder long axis (Group 2). In both groups, AO-like dynamic compression hole screws were positioned bicortically and neutrally. For each group, six specimens were tested until failure, three in bending and three in compression, to determine the loads for fatigue testing. Subsequently, for each group, 14 specimens were tested for failure --seven by bending and seven in compression. Results: No significant failure differences were observed between Groups 1 and 2 under static-loading or fatigue test. Clinical significance: In a fracture gap model the orientation of the locked monocortical screws did not show any influence on the mechanical performance of the S.P.S. Free-Block to tests of axial compression and four-point bending. © Schattauer 2013.
Keywords: Bone; Fatigue testing; Plate; Screw; Static testing; animal; animal disease; biomechanics; bone plate; bone screw; materials testing; mechanical stress; mechanics; Animals; Biomechanics; Bone Plates; Bone Screws; Materials Testing; Mechanics; Stress, Mechanical